Bisnis yang Bernilai Ibadah: Mengelola Rezeki Tanpa Melupakan Akhirat dalam Perspektif Hadis - Samsul Hilal; Muhammad Alif (Sinergi : Jurnal Ilmiah Multidisiplin, 2025)
Business activities are an integral part of human life and occupy a significant position in Islamic teachings. In the hadith tradition, business is not merely understood as an economic activity but also as a means of worship when conducted in accordance with ethical and spiritual principles. However, contemporary business practices often prioritize material profit while neglecting moral and eschatological dimensions. This article aims to examine the concept of business that holds devotional value from the perspective of hadith by analyzing its principles, ethical foundations, and spiritual orientations using a thematic hadith approach. This study employs a qualitative method with library research as its primary approach. Data were collected from authoritative hadith compilations through thematic searches using keywords related to business, trade ethics, sustenance (rizq), honesty, trustworthiness, and accountability in the hereafter. The data were analyzed through classification and interpretative content analysis techniques. The findings reveal that the Prophet Muhammad ﷺ emphasized the integration of worldly business activities with ukhrawi consciousness, highlighting principles such as honesty (ṣidq), trustworthiness (amānah), fairness (‘adl), and social responsibility. The hadiths also establish ethical boundaries in business practices, including the prohibition of fraud, deception, exploitation, usury, and injustice. Furthermore, business conducted with sincere intention and ethical commitment contributes not only to economic prosperity but also to spiritual growth and social welfare. Keywords: Business Ethics, Hadith, Worship-Oriented Business, Rizq, Thematic Hadith   Abstrak Aktivitas bisnis merupakan bagian integral dari kehidupan manusia dan memiliki kedudukan penting dalam ajaran Islam. Dalam perspektif hadis, bisnis tidak semata-mata dipahami sebagai aktivitas ekonomi, tetapi juga sebagai sarana ibadah apabila dijalankan sesuai dengan prinsip etika dan nilai spiritual. Namun, praktik bisnis kontemporer sering kali lebih menitikberatkan pada keuntungan material dan mengabaikan dimensi moral serta orientasi akhirat. Artikel ini bertujuan untuk mengkaji konsep bisnis yang bernilai ibadah dalam perspektif hadis dengan menelaah prinsip, landasan etika, dan orientasi spiritualnya melalui pendekatan hadis tematik. Penelitian ini menggunakan metode kualitatif dengan jenis penelitian kepustakaan (library research). Data dikumpulkan dari kitab-kitab hadis primer melalui penelusuran tematik menggunakan kata kunci yang berkaitan dengan bisnis, etika muamalah, rezeki, kejujuran, amanah, serta pertanggungjawaban di akhirat. Data tersebut dianalisis dengan teknik klasifikasi dan interpretasi konten hadis. Hasil penelitian menunjukkan bahwa Nabi Muhammad ﷺ menekankan keterpaduan antara aktivitas bisnis duniawi dan kesadaran ukhrawi melalui prinsip-prinsip seperti kejujuran (ṣidq), amanah, keadilan, dan tanggung jawab sosial. Hadis-hadis juga menetapkan batasan etis dalam praktik bisnis, seperti larangan penipuan, kecurangan, eksploitasi, riba, dan ketidakadilan. Selain itu, bisnis yang dijalankan dengan niat yang lurus dan komitmen etis tidak hanya berkontribusi pada kesejahteraan ekonomi, tetapi juga pada pertumbuhan spiritual dan kemaslahatan sosial. Kata kunci: Bisnis Bernilai Ibadah, Hadis, Etika Bisnis Islam, Rezeki, Hadis Tematik